Reabilitação oral por overdenture em paciente oncológico - Fagoni, Thalita Guarda [UNESP] (2015)
This paper aims to present a clinical case report of a patient irradiated in the head and neck region, with the necessity of oral rehabilitation, replacing the current prosthesis. The proposed treatment was composed by an upper complete denture and a lower overdenture supported by remaining dental roots. The purpose was to preserve the oral tissues preserving the root of anterior teeth, that simultaneously work keeping the alveolar bone as well as retaining the lower complete denture. The reported case allowed a treatment suited for the needs of this particular patient, restablishing function, phonetics and aesthetics.